HUBUNGAN ANTARA KUALITAS INPUT DAN MOTIVASI BELAJAR DENGAN HASIL BELAJAR SISWA KELAS X SMK PANCASILA SURAKARTA TAHUN PELAJARAN 2015/ 2016 - Permana, Muhammad Priya (Jurnal Nosel, 2016)
The objectives of the research are to investigate the following aspects: (1) the relationship between input quality and the learning outcomes of tenth grade students of Pancasila Vocational High School Surakarta, (2) the relationship between learning motivation and learning outcomes of tenth grade students of Pancasila Vocational High School Surakarta, and (3) the relationship between input quality and learning motivation simultaneously to learning outcomestenth grade students of Pancasila Vocational High School Surakarta. This research conducted is quantitative study, the data will be presented in the form of statistical calculations. The method used is correlational, which is intended to look for a causal relationship of the variables. The trial respondents were 30 tenth graders students. 75 students were selected as the sample from the population which consist of 167 studentsby using simple random sampling. The data were collected through questionnaires, interviews, and documentations. Validity test was done by using Pearson Product Moment correlation, while the Cronbach Apha formula was used to test the reability. To determine the effect of each predictor, input quality and learning motivation, to the learning outcomes, simple regression analysis was used, whereas to determine the relationship of input quality and learning motivation simultaneouslyto the learning outcomes, multiple regression analysis was used. The level of significance is 5%. The results showedthat: (1) There is a relationship between input quality(X1) and the learning outcomes (Y) proved by   of is greater than  of , (2) There is a relationship between learning motivation(X2) and learning outcomes(Y) proved by  of is greaterthan which is and (3) There is a relationshipbetween theinput quality(X1) and learning motivation(X2) withlearning outcomes(Y) proved by which is185,142is greater than which is to3,12.